Konsep Subyek Hukum Dalam Hukum Islam Dan Hukum Positif - Iqbal, Muhammad; Zulkifli, Zulkifli (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2026)
Indonesia, as a rule of law state that recognizes every person as an actor under the law, means that every person is recognized as a legal subject. The provisions regarding humans as legal subjects are regulated in Islamic law, referred to as mahk?m ?alaih, as mukallaf individuals. The term legal subject then continued to develop beyond individuals, namely legal entities. This paper aims to illustrate the differences and similarities in the concept of legal subjects in Islamic law and positive law. This research is a library study with a qualitative approach to examine the application of the legal subject concept in Islamic law and positive law in Indonesia. The main data source in this research is from written sources directly related to the study. In data analysis, the author uses qualitative analysis by coding data, reducing data, and drawing conclusions. The development of the term "legal entity" in Indonesia has progressed alongside the enactment of several Islamic laws and regulations, such as the law on waqf, the law on zakat management, the law on Religious Courts, the Compilation of Islamic Law, and the Compilation of Sharia Economic Law (KHES). The conclusion of this writing is that, in essence, Islamic Law is the command/message of God regarding the actions of the mukallaf, whether in the form of obligation (takl?f), choice (takhy?r), or determination (wad??). Islamic law according to Us?liyy?n is God's action in establishing the law, but according to Fuqah??, law is the effect or consequence of God's command/message. Meanwhile, positive law is the command and judgment regarding an action as good or bad, as well as the relationship between one person and an action of another person, which makes this person connect themselves with this action.